Pentagon: U.S. intercepted missiles from Iran (WP Company LLC d/b/a The Washington Post, 2024)
The Pentagon said on Oct. 1 that two U.S. Navy destroyers fired about a dozen interceptors against Iranian missiles aimed at Israel.